Comparative Analysis of Reading Habit and Translation Ability among Female and Male Students at STBA PIA Medan - Winaria Peggy Lovianna Simanjuntak; Bambang Nur Alamsyah Lubis (English Teaching and Linguistics Journal (ETLiJ), 2023)
The habit of reading will build and improve students' character and literacy. This habit will also help students become adequate readers, achieve a large vocabulary, understand and use complex grammatical constructions, and develop a good writing style. The reading habit of an individual depends on many factors, and one of those factors is gender. This research is aimed to compare the reading habits and translation skills of female and male students in English Literature Department at STBA PIA. The study is conducted at STBA PIA in Medan, North Sumatra. The sample, taken by random sampling, consists of 40 students, 20 female and 20 male students. The research design is a quantitative, analytical, and observational one. There are two instruments applied. A questionnaire is used to measure female and male students’ reading habits. Afterwards, the two groups of students are given a translation test to get data about their ability to translate. The test uses the scale instrument of holistic-based translation quality assessment (TQA). The distribution frequency of the collected data is analyzed using univariate analysis. An independent T-test (two-tail) will be conducted to find out the comparative data on reading habits and translation skills between female and male students.